The Ecological Values in the Sedekah Bumi Ceremony in Kalitanjung Hamlet, Banyumas Regency - Arifah, Aprilia Rizki; Winarni, Retno; Suhita, Raheni (Humaniora: Journal of Indonesia Culture and Society, 2025)
The issue of ecology has gained global attention due to widespread environmental damage, including in Indonesia. Our ancestors possessed local wisdom that helped preserve ecological balance, one example being the Sedekah Bumi (earth alms) tradition in Banyumas, Central Java, Indonesia. This research aims to examine the values of ecological wisdom and the role of the Sedekah Bumi ceremony in shaping the community's ecological awareness, particularly through the processions and offerings made in Kalitanjung Hamlet, Banyumas Regency. Additionally, it explores how the indigenous people of Banyumas have managed to preserve this tradition to this day. This research employs a qualitative descriptive research design with an ethnographic approach. Data collection techniques included observation, in-depth interviews, and document analysis. The theoretical framework for this research is based on Keraf's nine principles of environmental ethics. The findings reveal that the ecological wisdom inherent in the Sedekah Bumi tradition is closely linked to the community's way of life. This deep connection with nature has given rise to nine key ecological values: respect for nature, moral responsibility for nature, cosmic solidarity, care for nature, the principle of "no harm," simplicity and harmony with nature, justice, democracy, and moral integrity. This research contributes to existing theories and provides practical implications for further studies on the Sedekah Bumi tradition in various regions.